An unusual massive lipoma in anterior neck, partially engulfing the carotid artery and internal jugular vein: a case report with review of literature - Mantri, Gaveshani; Patsani, Monalisa; Mohanty, Rahul; Aparajita, Aishwarya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
A lipoma is a benign mass, but when big in size and present at an unusual location, it can pose major diagnostic and therapeutic challenges. We report a rare case of a big lipoma in the neck which partly engulfed the internal jugular vein (IJV) and carotid artery. The lipoma was removed in toto and the patient was followed up. This mass was unusual due to its size, behaviour and location. The report also includes a literature review about the unusual behaviour of lipomas at such rare sites and the management options available.